2022
DOI: 10.1155/2022/5692298
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling, Simulation, and Analysis of the End-Milling Process Using DEFORM-3D with Experimental Validation

Abstract: In this present work, finite element analysis (FEA)-based simulation of end-milling of AISI1045 steel using tungsten carbide tool was performed using DEFORM-3D simulation software. Usui tool wear model, Johnson-cook material model and adaptive remeshing are considered during machining simulation. The impact of machining variables rate of feed, tool speed, and depth of cut was investigated, and the best integration of variables was distinguished for lower cutting temperature, principal stress, cutting forces, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 48 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…The forming process uses the Johnson-Cook material model and the Lagrangian incremental (LE) method of mathematical formulation. Equation 2 illustrates the strain rate and temperature dependent equation for the work piece's isotropic behavior with deformable thermo-viscoplastic property [26].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The forming process uses the Johnson-Cook material model and the Lagrangian incremental (LE) method of mathematical formulation. Equation 2 illustrates the strain rate and temperature dependent equation for the work piece's isotropic behavior with deformable thermo-viscoplastic property [26].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This experiment demonstrated that the needed creep qualities should meet using the non-isothermal processing technique with the correct thermomechanical process parameters selection. The experiment was conducted on AISI1045 steel end-milling with a tungsten carbide tool and used finite element analysis-based modeling using DEFORM-3D software to minimize temperature, stress, thrust force, tool wear geometry, and strain [26].…”
Section: Introductionmentioning
confidence: 99%